Import substitution, export promotion and the state in economic development. - GRABOWSKI, Richard (1994)
Argues that import substitution and export-based growth are alternative ways for stimulating the growth in the size of markets for manufactured goods. Contends that import substitution is generally necessary for outward-oriented growth to succeed, and, more important, the success of import substitution is linked to the development of productivity in the agricultural sector. Discusses the relationship between market growth and state behaviour.